Improving Students’ Writing Ability through Jeopardy Game at the Second Grade Students of Junior High School - Arwandi, Nurfitrah; Suparmi; Dania, Rahma; Alhusna, Asma (IPI Garut Press, 2025)
This research aimed to determine the impact of using Jeopardy games on improving students’ writing ability in learning English at Junior High School state 2 in Padang. Jeopardy game is a guessing game type with a unique rule, which the clues in statements form and answers in questions form, allowing players to think critically and creatively. This research used a quantitative research with a pre-experimental approach and data collection was carried out using pre-test and post-test to analyze the effect of using Jeopardy games on students who consisted of 32 students from class VIII, who were selected using cluster random sampling. The research results show that Jeopardy games can improve students’ writing ability. The pre-test result showed average score was 47,88 and the post-test was 70,89. After data was collected, the data was analyzed using t-test formula. The result of the analysis showed that the value of t-test > t table is 9,802 > 2,042. The last hypothesis shows that (Ho) is rejected and (Ha) is accepted. It means there is a significant influence on improving students’ writing ability using Jeopardy game.